(untitled) - Fuller, Mark B. (New York, NY., 2006)
By returning to fundamental Japanese philosophies and blending them with modern management approaches, Japanese corporations were able to overcome the challenges of a slow-growth economy, reinvigorate their businesses and in the process spur economic renewal for the country. Through a detailed examination of these methods as well as illustrative examples from companies that include Nippon, Kyocera, Toyota, and Sony, Fuller and Beck provide a roadmap all managers can use to spark growth in their own organisations. When Japanese businesses failed to focus on the principles and methods that made the country one of the world's leading industrial nations, the economy ground to a standstill and the country ceased to be a threat to global competitors. In the last three years, Japan's economy and business leadership rebounded dramatically ndash; a turnaround that business leaders attribute to Bushido, the Samurai philosophy that holds renewal at its core The book looks at how Japanese business leaders transformed their companies in the face of a no-growth economy, delivering a role model for companies the word over faced with similar challenges This is the first book to date that looks at how Japanese philosophies are being applied to modern day business strategy, which is currently receiving tremendous exposure in the press This will be a flagship book for the Monitor Group, a highly prestigious management consultancy with offices in 28 countries Mark Fuller, the Chairman of the Monitor Group and acclaimed author John Beck deliver lessons drawn from Japanese business leaders on revitalizing growth in a down economy and shows how companies the world over have used methods borne from Japanese philosophy to transform their own organizations The authors will promote the book through Monitor Group offices around the world, its extensive email list (17,000 names), and will use its contacts to publish articles in key business magazines at the time of publication.
Keywords: Management,Corporations, Foreign,Leadership,Success in business,Industrial management; Japan,Japan